Integration of Video Tutorial Screencast Sketchup Make (VTS-SUM) To Enhance Students’ Visual Spatial Skills - Yahya, Faridah Hanim; Adenan, Nur Hamiza; Murtafiah, Wasilatul; Shamsuddin, Norin Rahayu (CENTRAL ASIA AND THE CAUCASUS, 2022)
Problems in learning 3-dimentional Geometry are related to a low level of visual spatial skills. The purpose of this study is to test a learning approach, using video tutorial screencast SketchUp Make, or VTS-SUM. The approach combines screencast video and 3D software for topic Plans and Elevations. SketchUp Make is a free 3D software, which can be downloaded from the internet. Using this software, students were trained to rotate, view, transform and cut objects, using tools provided to enhance their visual spatial skills, before drawing the plan and elevations of the objects. The video tutorials demonstrate steps in using the software. The study involved a total of 54 Form-Three high achievers, 25 of whom were male and 29 female. The study was conducted for six weeks using a quasi-experimental single group design, in the form of pre-posttest. The instruments used for this study were selected from visual spatial mental tests and the data obtained was analyzed, using paired sample t-test. The results showed that, there were significant differences in the mean scores of visual spatial skills, before and after learning via VTS-SUM (t=26.87; p<0.05). Hence, learning via VTS-SUM proved to be effective to enhance the students’ level of visual spatial skills.